The history and sociology of genocide : analyses and case studies - Chalk, Frank Robert; Jonassohn, Kurt (London : Yale University Press, 1990)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: genocide; sociologisch onderzoek